Assessing psychiatric safety in suicidal emergency department patients. Issue 1 (29th January 2020) - Brenner, Jay M.; Marco, Catherine A.; Kluesner, Nicholas H.; Schears, Raquel M.; Martin, Daniel R.
Abstract: We provide a review of the assessment of suicidal emergency department patients and includes a legal and ethical perspective. Screening tools and psychiatric consultation are important adjuncts to the ED evaluation of potentially suicidal patients. Suicide risk should be assessed, and if positive, an appropriate and safe disposition should be arranged. The aim of this article is to review these assessment tools and consider ethical issues, such as patient autonomy, accountability of the emergency physician, and consultant to Emergency Medical Treatment and Labor Act (EMTALA) as well as confidentiality, privacy, and social issues.